Memahami Landasan Biblis Moralitas Katolik dan Relevansinya bagi Perwujudan Bonum Commune - Megawati Naibaho; Martina Rosmaulina Marbun; Yanti Vidarosa Naibaho; Fidelis Den; Clara Cici Ceriawati Waruwu (Jurnal Magistra, 2026)
Catholic moral teachings are not merely ethical codes, principles, rules, or prohibitions to prevent humans from falling into sin. Catholic morality has a solid foundation that originates from the Word of God. The problem to be explored in this study is the phenomenon of ignorance among believers who assume that morality as a rule taught by the Church only restricts the freedom of believers. The purpose of this study is to present the foundation of Catholic moral teachings so that believers know and are able to understand and implement them with the right and appropriate attitude. Thus, believers have a correct understanding. The method used is a literature study. The results of this study explain that Catholic morality is a response to the aspirations of the human heart for truth and goodness. Thus, this study offers clear and precise guidelines for when implemented to achieve the common good and welfare, namely bonum commune. Catholic morality is not an oppressive principle, but a practical guide to a good life.